Green Human Resources Management to the Work Enviroment at Hotel Puri Jaya Central Jakarta - Marlianingrum, Peggy Ratna; Aprilia, Indah (PT FORMOSA CENDEKIA GLOBAL, 2025)
Green Human Resource Management (GHRM) involves various hospitality industries that are closely related such as accommodation/lodging, restaurants, tour guides to maintain the environment and sustainability of a company. This study aims to see the implementation of GHRM that supports the work environment of the hospitality industry and to see the dimensions of GHRM in supporting environmental performance. The method used is quantitative research, using questionnaires distributed to 50 hotel employees. The study's findings indicate that the factors of green recruitment/selection and green training have a good and significant impact on the workplace, partially and concurrently. The implementation of GHRM needs to be done when recruiting prospective employees by providing information about having environmental management competencies. Employees must also receive training from the organization on how to create a green workplace that makes them feel safe and comfortable.